Tax equity, green innovation and corporate sustainable development - Wang, Wei (Frontiers in Environmental Science, 2022)
In the context of increasing resource scarcity and environmental pollution, achieving sustainable development with environmental friendliness at its core is essential for maintaining long-term economic growth. However, the positive environmental externalities associated with sustainable development impose an additional cost burden on enterprises. Internalizing those positive environmental externalities in the form of corporate benefits through tax policies is the key to incentivizing sustainable development. Using the reform of China’s tax enforcement agency and tax enforcement system as a quasi-natural experimental context, this paper investigates the impact of tax equity on sustainable development. The empirical findings show that tax equity can promote the sustainable development of enterprises, and this promotion is achieved by enhancing corporate green innovation. Furthermore, tax equity has a stronger effect on the sustainable development of enterprises in a favorable market environment because it is more conducive to the protection of intellectual property and transformation of green innovation into tangible output. The tax equities brought about by different types of tax reforms have different effects on the sustainable development of enterprises in different life cycle stages because the types of tax inequities suffered by enterprises of different ages vary.